2017
DOI: 10.24896/jmbr.2017722
|View full text |Cite
|
Sign up to set email alerts
|

The effects of storage on the bacteriological quality of sachet water produced, sold and consumed within Owerri Metropolis, Imo State, Nigeria

Abstract: The sale and consumption of sachet water is common in Owerri metropolis because the consumers believed it was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…According to the authors, most of the water samples had pH in the range of 6.85-7.37, with a steady increase during storage. The results are also in line with what was reported by Unegbu[28]. The pH of drinking water is critical to its sensory properties as pH outside the WHO/NIS acceptable range of 6.5-8.5 may constitute an undesirable taste[32].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…According to the authors, most of the water samples had pH in the range of 6.85-7.37, with a steady increase during storage. The results are also in line with what was reported by Unegbu[28]. The pH of drinking water is critical to its sensory properties as pH outside the WHO/NIS acceptable range of 6.5-8.5 may constitute an undesirable taste[32].…”
supporting
confidence: 90%
“…The increasing electrical conductivity could be associated with rising levels of dissolved materials in the water samples during storage [40]. An elevated temperature of stored sachet water has also been linked to higher electrical conductivity [28]. Electrical conductivity denotes the ability of water to conduct electricity.…”
Section: Resultsmentioning
confidence: 99%
“…They found that 90% of the analysis results complied with WHO/NIS guidelines for quality water, with total coliforms, fecal coliforms, and enterococci absent in the water samples. Unegbu et al (2017) studied the effect of storage on the physicochemical properties of sachet water in Owerri. They observed that after eight weeks of storage, oxygen, chlorine, alkalinity, and BOD decreased, while temperature, calcium, magnesium, total hardness, total dissolved solids, and electrical conductivity increased.…”
Section: Literature Reviewmentioning
confidence: 99%